Expression Profile Analysis of Long Non-coding RNA in OVX Models-Derived BMSCs for Postmenopausal Osteoporosis by RNA Sequencing and Bioinformatics - Gu, Huijie; Huang, Zhongyue; Zhou, Kaifeng; Chen, Guangnan; Bian, Chong; Xu, Jun; Yin, Xiaofan (Frontiers in Cell and Developmental Biology, 2021)
Osteoporosis (OP) has the characteristics of a systematically impaired bone mass, strength, and microstructure. Long non-coding RNAs (lncRNAs) are longer than 200 nt, and their functions in osteoporosis is yet not completely understood. We first harvested the bone marrow mesenchymal stem cells (BMSCs) from ovariectomy (OVX) and sham mice. Then, we systematically analyzed the differential expressions of lncRNAs and messenger RNAs (mRNAs) and constructed lncRNA–mRNA coexpression network in order to identify the function of lncRNA in osteoporosis. Totally, we screened 743 lncRNAs (461 upregulated lncRNAs and 282 downregulated lncRNAs) and 240 mRNAs (128 upregulated and 112 downregulated) with significantly differential expressions in OP compared to normal. We conducted Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) functional analyses to investigate the functions and pathways of the differential expression of messenger RNAs (mRNAs), a coexpressed network of lncRNA/mRNA. Quantitative PCR (qPCR) validated that the expressions of NONMMUT096150.1, NONMMUT083450.1, and NONMMUT029743.2 were all downregulated, whereas NONMMUT026970.2, NONMMUT051734.2, NONMMUT003617.2, and NONMMUT034049.2 were all upregulated in the OVX group. NONMMUT096150.1, as a key lncRNA in OP, was identified to modulate the adipogenesis of BMSCs. Further analysis suggested that NONMMUT096150.1 might modulate the adipogenesis of BMSCs via the peroxisome proliferator-activated receptor (PPAR) signaling pathway, AMPK signaling pathway, and the lipolysis regulation in adipocyte and adipocytokine signaling pathway. Our study expands the understanding of lncRNA in the pathogenesis of OP.